Structural and cellular insights into DCTPP1 antagonists and their synergistic action with DNMT inhibitors - Glenn Hauk; Jianyong Liu; William G. Nelson; Srinivasan Yegnasubramanian; James M. Berger (Proceedings of the National Academy of Sciences, 2026)
DCTPP1 is a nucleotide pyrophosphatase that helps preserve genomic stability and epigenetic programming by hydrolyzing and preventing the misincorporation of methylated base-modified deoxycytosine triphosphates into DNA. Through this role, DCTPP1 can degrade the efficacy of nucleotide analog-based DNA methyltransferase inhibitors and thus represents a compelling therapeutic target in cancer treatment. To identify prospective antagonists of DCTPP1, we conducted a high-throughput chemical screen against the enzyme, identifying both existing and previously unreported inhibitor classes with potent submicromolar activity. Structural characterization using X-ray crystallography revealed that the inhibitors all occupy DCTPP1’s nucleotide-binding pocket, associating primarily with a pair of tryptophans and two critical histidine residues that mimic interactions observed with natural substrates. Biochemical assays using modified chemical scaffolds confirmed the relevancy of the observed DCTPP1–antagonist interactions, while cell-based experiments demonstrated significant synergy between the lead inhibitors and the nucleoside analog decitabine in blocking the growth of prostate cancer cells. The specificity and efficacy of the compounds were further validated through loss- and gain-of-function studies, confirming the dependence of their therapeutic synergy on DCTPP1 activity. These findings advance our understanding of DCTPP1 as a therapeutic target while uncovering chemical scaffolds that can potentiate the action of existing nucleotide-based cancer therapies.